Pengaruh Lama Perendaman Terhadap Perkecambahan Dan Pertumbuhan Tanaman Palem Raja - Dwi Wahyu Setyaningsih (Universitas Merdeka Madiun, 2018)
Abstract— Plant germination is the beginning of a new individual's growth marked by the appearance of a radicle at the seed testa. This research aims to determine the effect of long immersion towards germination and growth of King Palm. This study used an experimental method with Randomized Block Design (RBD) with 4 treatments and 4 repetitions. Those treatments were treatment of P0 (control), P1 (immersion for 24 hours), P2 (immersion for 48 hours) and P3 (immersion for 72 hours). The data obtained was analyzed by variance analysis and continued with BNT test. Based on observations, King Palm seed germination is hypogeal, because cotyledons (keeping seeds) remain in the soil. King palm seeds with immersion treatment do not significantly affect germination. Likewise, immersion time does not significantly affect the height of shoots aged 55 days after seedling. The treatment of immersion time for King Palm seeds significantly affected the root length at the age of 55 days after seedling. After the BNT test, the effect of immersion towards the root length showed that 48 hours of immersion treatment had the best effect. The 48-hour immersion treatment for the King Palm plant nursery is recommended to be done by ornamental plant farmers and ornamental plant breeders to accelerate the growth process.Keywords—: King's Palm, Germination, Growth, Hypogeal.